Effect of risks on earnings and the US bank share valuation - Cheng, Fan Fah; Ramadilli Mohd, Shamsher Mohamad; Md Nasir, Annuar (Universiti Putra Malaysia Press, 2013)
The financial crisis of 2008 had a great impact on the banking industry of the United States. This paper looks at the impact of the financial risks on the share revaluation of commercial banks in United States. It is expected that the earnings announcements will affect investors' decisions to trade in bank shares. The Earnings Response Coefficients (ERCs) are applied in this paper to ascertain whether the estimated financial risks have incremental information content beyond the reported earnings. The findings support the notion that investors in the United States do look beyond the reported numbers and look for credit, market and price risk significantly in the earnings response valuation among other financial risks variables.